2012
DOI: 10.1111/j.1751-2980.2012.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

The proliferative effects of ghrelin on human gastric cancer AGS cells

Abstract: Ghrelin and des-acyl ghrelin stimulate the proliferation of gastric cancer cells via the activation of the ERK1/2 and PI3K/Akt pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
2
18
1
1
Order By: Relevance
“…The results of this study provide the first evidence that ghrelin does not affect cancer progression in lung adenocarcinoma. Although a considerable body of in vitro researches indicated that ghrelin might affect cancer progression via several signaling pathways, e.g., PI3K/Akt [9] and Erk1/2 [10], our findings demonstrate that ghrelin treatment did not influence biological activities, viability, proliferation, or resistance to apoptosis in human lung adenocarcinoma HLC-1 cells. In normal cells, ghrelin promotes proliferation by stimulating the PI3K/AKT pathway and MAPK pathways [11], and also increases resistance to apoptosis [12].…”
Section: Discussioncontrasting
confidence: 72%
“…The results of this study provide the first evidence that ghrelin does not affect cancer progression in lung adenocarcinoma. Although a considerable body of in vitro researches indicated that ghrelin might affect cancer progression via several signaling pathways, e.g., PI3K/Akt [9] and Erk1/2 [10], our findings demonstrate that ghrelin treatment did not influence biological activities, viability, proliferation, or resistance to apoptosis in human lung adenocarcinoma HLC-1 cells. In normal cells, ghrelin promotes proliferation by stimulating the PI3K/AKT pathway and MAPK pathways [11], and also increases resistance to apoptosis [12].…”
Section: Discussioncontrasting
confidence: 72%
“…Several factors mediate the metastatic capacity of gastric carcinoma through the PI3K/Akt/mTOR pathway [ 61 , 62 , 63 , 64 , 65 ]. Administration of 2-methoxyestradiol, a metabolite of estradiol-17b, decreased cell invasion and metastasis of gastric carcinoma through attenuation of Akt activity [ 66 ].…”
Section: The Role Of the Pi3k/akt/mtor Pathway In The Biological Pmentioning
confidence: 99%
“…The highest levels of ghrelin are found in the small intestine, pancreatic islet cells, gallbladder, liver, spleen and immune cells (10). Recent evidence has demonstrated that ghrelin has dual proliferative effects, according to the type of cell or tissue, via mechanisms that are dependent on or independent of GHS-R1a (11). In addition, ghrelin has possible antioxidant and anti-inflammatory effects (7,12).…”
Section: Introductionmentioning
confidence: 99%